Microbial Community Structure and Functional Potential of Deep-Sea Sediments on Low Activity Hydrothermal Area in the Central Indian Ridge - Namirimu, Teddy; Kim, Yun Jae; Park, Mi-Jeong; Lim, Dhongil; Lee, Jung-Hyun; Kwon, Kae Kyoung (Frontiers in Marine Science, 2022)
Little is known about the community structure and metabolic potential of microbial communities in hydrothermal fields in the Central Indian Ridge (CIR). In this study, a metagenomic sequencing approach was conducted to explore the microbial diversity in three sediment samples collected during the 2019 expedition from two recently discovered hydrothermal vent fields; Invent E and Onnuri Vent Field (OVF). Analysis of unassembled metagenomic reads using the Metagenomic analysis server (MG-RAST) revealed that microbial communities of the two sampling sites were very similar, showing dominance of Bacteria over Archaea. Proteobacteria, Firmicutes, Bacteriodetes, as well as Euryarchaeota were dominant in all samples. Functional annotation based on KEGG categories shows that the microbial populations in these vent fields possess metabolic capabilities for aerobic respiration, carbon fixation through the Calvin-Bassham-Benson (CBB) cycle, the reverse tricarboxylic acid (rTCA) cycle, and reductive acetyl-CoA pathway as well as sulfur and nitrogen metabolisms. Comparative metagenome analysis with different datasets obtained from different ocean ridges showed that microbial communities at low activity or hydrothermally influenced area differ from highly active hydrothermal communities. This study provides insights into the genetic diversity and functional capability of the microbial communities of slow to intermediate spreading hydrothermal systems.